Millimeter and submillimeter studies on the active trinity of gas, stars, and black holes in Seyfert galaxies : doctoral thesis accepted by The University of Tokyo, Tokyo, Japan /: doctoral thesis accepted by The University of Tokyo, Tokyo, Japan. ([2018]) - Izumi, Takuma
No abstract available